Pembuatan Aplikasi Augmented Reality Terkait Bisnis Pelayanan Infrastruktur PT. PLN Batam - Nurdiansyah, Dian; Riyadi, Agung (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2023)
The use of Augmented Reality (AR) technology in promoting the infrastructure service business of PLN Batam will provide a more interactive and enjoyable experience for the community. However, many infrastructure service companies have not yet utilized this technology to promote their business. Therefore, this research aims to develop an augmented reality application related to the infrastructure service business of PT. PLN Batam using the waterfall research methodology on the Unity platform. The research will be conducted in stages following the waterfall methodology, starting from user needs analysis to application testing. The development of this AR application will utilize the Unity platform as the application development tool and also utilize Vuforia as a plugin for detecting target markers. The results of this research are expected to provide a solution for PT. PLN Batam to utilize AR technology in promoting their business, introducing the company to the community, and strengthening its reputation as a trusted and professional infrastructure service provider.